Neuroprotective Potential of Lantana Trifolium Ethanolic Extract against Ethambutol Induced Histological Changes in the Optic Nerve - Owembabazi, Elna; Ninsiima, Herbert Izo; Mario, Edgar Fernandez Diaz; Echoru, Isaac; Lemuel, Ann Monima; Ahimbisibwe, James; Bukenya, Edmund (Anatomy Journal of Africa, 2017)
Ethambutol is an anti-tuberculosis drug important in treatment of multidrug resistant tuberculosis which is on a rise due to emergence of Human Immunodeficiency Virus. However, it has been associated with side effects on optic nerve histology leading to severe neuropathy. The purpose of this study was to establish the protective potential of Lantana trifolium ethanolic extract against ethambutol induced histological changes in the optic nerve. Twenty five male adult wistar rats of 110-130g average weight were used. These were divided into five groups each comprising five animals. Group A received distilled water only. Group B was treated with 100 mg/kg/day of ethambutol. Groups C, D, and E were treated with 25, 50, and 100 mg/kg/day of Trifolium Extract respectively, one hour before administering 100 mg/kg/day of ethambutol. After five weeks the optic nerves were excised, processed and stained for histological studies. It was observed that Lantana trifolium ethanolic extract had a dose dependent protective potential against ethambutol induced histological changes in the optic nerve. The histology of the optic nerve showed that the numbers of vacuoles were significantly few in group A (2.2±0.37), D (6.2±1.07), and E (5±0.71) when compared against the positive control group (37.4±1.54). Axons were mildly demyelinated in group D and E compared to group B and C. The protective potential of Latana trifolium is possibly present due to its anti-oxidative and anti-inflammatory activities. Studies to determine the exact phytochemical component and mechanism of action responsible for the neuroprotective potential of Latana trifolium should be conducted.
Keywords: Ethambutol; Optic Nerve; Lantana Trifolium; Optic Neuropathy